Analysis of Zakat Accounting at the Lazismu Regional Leadership of Muhammadiyah Bulukumba Regency - Suarni, Agusdiwana; Rizal, Samsul; Kumala, Kumala (Invoice : Jurnal Ilmu Akuntansi, 2024)
The purpose of this study was to identify and analyze accounting confirmations, analyze the accounting records of zakat by the leadership of the LAZISMU Muhammadiyah region, Bulukumba Regency, and describe the application of zakat accounting to the leadership of LAZISMU Muhammadiyah, Bulukumba Regency. The results of this study indicate that currently the recognition of zakat, infaq and shadaqah funds for the Regional Leadership of LAZISMU Muhammadiyah Bulukumba Regency is only recorded if cash receipts and disbursements have occurred. This statement is in accordance with PSAK 109 which states that zakat, infaq and shadaqah are recognized when cash or other assets are received. The presentation used by LAZISMU Regional Leaders of Muhammadiyah Bulukumba Regency was declared not in accordance with PSAK 109 because the five components of the PSAK 109 report. LAZISMU only used two financial reports and even that was not appropriate. The presentation is also expected to be more clear and transparent, because in this case it will increase public confidence in the transfer of zakat funds, information and shadaka to the regional leadership of LAZISMU, Bulukumba Regency. Disclosure at the Regional Leadership of LAZISMU Muhammadiyah Regency is not fully in accordance with PSAK 109 because it is not clearly detailed.